2018
DOI: 10.1007/s11999.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Can Patient Selection Explain the Obesity Paradox in Orthopaedic Hip Surgery? An Analysis of the ACS-NSQIP Registry

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Age, comorbidities and increased ASA class are known risk factors for complications after hip fracture surgery 17 , 18 . Nutritional status, malnourishment, as well as obesity, may also have an effect in increasing risk for complications 19 . We did not use the Nottingham score, and there is without doubt several patient factors that may have contributed to outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Age, comorbidities and increased ASA class are known risk factors for complications after hip fracture surgery 17 , 18 . Nutritional status, malnourishment, as well as obesity, may also have an effect in increasing risk for complications 19 . We did not use the Nottingham score, and there is without doubt several patient factors that may have contributed to outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Когортные исследования свидетельствуют о связи между наличием Ож и развитием нозокомиальных инфекций в послеоперационном периоде, в частности после сердечно-сосудистых, ортопедических, гастроэнтерологических операций [28,33,34]. В нескольких исследованиях была показана более высокая частота инфекций в послеоперационном периоде у больных, подвергнутых операции аорто-коронарного шунтирования [35,36].…”
Section: нозокомиальные инфекцииunclassified
“…In their study of more than 91,000 patients, Zhang and colleagues [5] found that patients with morbid obesity (> 40 kg/m2) who underwent nonurgent hip surgery between 2011 and 2014 were less likely to die and less likely to have cardiac and respiratory complications within 30 days compared to patients with a normal weight (18.5–24.9 kg/m2). They also found that patients with morbid obesity and patients with normal weight who underwent urgent hip surgery had no differences in their odds of death within 30 days.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Zhang and colleagues [5] contend that the obesity paradox may be the result of preoperative patient selection. Indeed, it does seem to me that more attention is being paid of late to ensuring that patients are both well selected and as medically prepared as possible for elective hip surgery.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation